Challenges to effective utilization of entrepreneurial skills of unemployed graduates in Damaturu Yobe State, Nigeria - Usman, Hassan A. (Kashere Journal of Education, 2023)
The purpose of acquiring entrepreneurial skills not even only for undergraduates is to secure a living or self-reliance using creative talent to establish a venture that will ensure and sustain growth of wealth in the entrepreneur personal economic and the country at large. This is not possible to the developing entrepreneurs’ consequent to a certain number of challenges that affect the effective utilization of such skills which attributed to unemployment and redundancy among undergraduates. This study aimed at identifying the skills required by unemployed graduate for self-reliance and the challenges to effective utilization of entrepreneurial skills of unemployed graduates in Damaturu Educational Zone. The research study was carried out in four local government areas in Damaturu Educational Zone. The target population consists of 230 unemployed graduates who undergo skills acquisition and empowerment Development (SAED) program in NYSC Camp. A structured questionnaire was used. Finding reveals that lack of capital, lack of mentoring and guidance, too much dependence on government employment among others are among the challenges facing the unemployed graduates to use entrepreneurship skills effectively in their various destinations. It was recommended that some of the business organizations and Yobe State Government should come up with a novel way to support the unemployed graduates with grant for start-ups, private sectors and authorities should also provide simplified access to fund at reliable financial agencies, the unemployed graduates entrepreneurs should as much as possible obtain a start-up capital for the venture from funding institutions and must not depend on government for employment among others.